Clinical effect analysis of posterior longitudinal ligament resection during anterior cervical discectomy and fusion in the treatment of cervical spondylotic myelopathy - NIU Hai‐ying; MENG Xiang‐yu; ZUO Shan‐shan; SUN Xiao‐li; LI Yan; LIU Hong‐lei (Chinese Journal of Contemporary Neurology and Neurosurgery)
Objective To investigate the effect and safety of microscopic posterior longitudinal ligament resection during anterior cervical discectomy and fusion (ACDF) in the treatment of cervical spondylotic myelopathy (CSM). Methods A total of 38 patients with CSM completed resection of posterior longitudinal ligament during ACDF under microscopy were enrolled in The First Hospital of Hebei Medical University from August 2023 to August 2024. The modified Japanese Orthopedic Association Scores (mJOA) was used to assess spinal cord function, Visual Analog Scales (VAS) was used to assess neck and upper limb pain, and Neck Disability Index (NDI) was used to assess the degree of cervical dysfunction before and 3 months after surgery. The operation⁃related complications within 3 months after surgery such as limb dysfunction, drinking cough, hoarseness, pharyngeal pain and incision infection were counted. Results All 38 patients experienced successful surgery, with a success rate of 100%. And at 3 months after surgery, there were significant improvements compared to preoperative values: the mJOA score increased (t = 5.225, P = 0.000), while VAS score (Z = ⁃ 4.029, P = 0.000) and NDI score (Z = ⁃ 3.915, P = 0.000) decreased. There were 30 patients (78.95%) experienced transient symptoms, including dysphagia, pharyngeal pain and drinking cough, 15 patients (39.47%) reported symptoms of hoarseness, 3 patients (7.89%) experienced a transient decrease in muscle strength in the left upper limb, and one patient (2.63%) had cerebrospinal fluid leakage. Notably, no patients exhibited incomplete healing of the incision or infection. Conclusions The degenerative hyperplasia of the posterior longitudinal ligament of the cervical spine is an important factor of spinal cord compression in CSM. The posterior longitudinal ligament resection under the microscopy can decompress the diseased segment more thoroughly and significantly improve spinal cord function.